PENGARUH KEAMANAN DAN KESELAMATAN TERHADAP CITRA DESTINASI DI OBYEK WISATA ALAM AIR TERJUN SRI GETHUK GUNUNGKIDUL - Fian Damasdino; Dian Afrini; Pri hatno (Journal of Tourism and Economic, 2021)
This study aims to see if there is an influence between the security and safety of tourists on the image of tourist destinations at Sri Gethuk Waterfall, Gunungkidul. This study uses quantitative research methods with 100 respondents from tourists who have visited Sri Gethuk Waterfall in the last one year. Collecting data using observation, questionnaires, and library documentation. The results show that there is an influence between the security and safety of tourists simultaneously on the image of the destination, while the Coefficient of Determination Test shows that the image of a tourist destination is influenced by the security and safety of tourists by 78.1%, while the remaining 21.9% is explained by other factors not examined in this study.